(untitled) (Research, Society and Development, 2021)
To understand the perception of nurses in quality management of nursing care at a public health institution in Brazil. Qualitative research was carried out with participation of 18 nurses. Conducted with an interview, open questions with independent variables: characterization of professionals and outcome (perception of quality management, before - 1st phase - and after - 2nd phase - the intervention). Data organized with the help of ATLAS.ti software, Bardin analysis, with the theme “Delivery of value” in the first phase and the theme “Quality indicators focusing on delivering results” in the second phase. The third theme, “Management of care”, in 2 phases. Results showed that the perception of nursing managers about quality management varied between the first and second phases. Considering the revelations about scarce knowledge about quality management, we point out the need to carry out training with a health management approach focused on the management of the quality of care.